Hydrogen gas detecting material having Ag-Pd-Au alloy core and metallic oxide shell structure and its manufacturing method, and semiconductor type gas sensor for detecting hydrogen gas using the same
Patent Information
- Application Number
- KR1020230016200
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-02-07
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2043-02-07
Smart Images

Figure 112023014246309-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure, a method for manufacturing the same, and a semiconductor gas sensor for detecting hydrogen gas using the same. More specifically, the invention relates to a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure that exhibits characteristics in which the reactivity to hydrogen gas is rapidly improved in a shell layer made of a metal oxide by selectively promoting the oxidation reaction of hydrogen gas using Ag-Pd-Au ternary alloy nanoparticles with hydrogen absorption capacity as a core, and a method for manufacturing the same and a semiconductor gas sensor for detecting hydrogen gas using the same. Background Technology
[0002] Generally, a characteristic of semiconductor gas sensors is that when gas is adsorbed onto the sensor surface, it exhibits a change in electrical conductivity within a specific temperature range. This phenomenon is triggered by the movement of electrons between the gas and the surface of the sensing material, causing an increase or decrease in conductivity depending on the properties of the sensing material.
[0003] A gas sensor system is constructed by connecting these electrical changes to a simple electrical circuit, and the constructed system is characterized by its low cost and rapid response characteristics.
[0004] Materials commonly used as sensing materials for semiconductor gas sensors include N-type and P-type semiconductors. N-type semiconductor materials include SnO2, TiO2, ZnO, WO3, and In2O3, while P-type semiconductor materials include CuO, Cu2O, NiO, Cr2O3, and Co3O4.
[0005] In general, N-type semiconductor materials are more widely used as sensing materials for gas sensors because of their excellent reactivity to gases.
[0006] The gas detection principle of metal oxide semiconductor nanoparticles is explained as follows, using an N-type semiconductor sensing material as an example.
[0007] When metal oxide nanoparticles are heated to 300–400°C in the atmosphere, thermal energy is supplied within the nanoparticles, generating many free electrons, and at the surface of these nanoparticles, oxygen (O2) from the atmosphere captures the electrons within the nanoparticles, causing O - It becomes adsorbed in that state.
[0008] As a result, an electron depletion layer with almost no electrons is formed on the surface layer of the metal oxide nanoparticles, and the electrical resistance of the metal oxide becomes high.
[0009] At this time, when reducing gases (CO, H2, NO, VOCs, etc.) are supplied to the surface of the metal oxide, these gases react with oxygen ions and are oxidized, and the free electrons captured by the oxygen gas return to the metal oxide, thereby lowering the electrical resistance of the metal oxide.
[0010] It detects the presence and concentration of reducing gas by utilizing these changes in electrical resistance.
[0011] However, since N-type semiconductor sensing materials alone lack sufficient gas sensing capability, precious metal catalysts such as platinum, palladium, and gold are generally coated on the oxide surface.
[0012] Here, precious metal catalysts play two roles: one is a chemical catalytic effect, and the other is an electronic effect.
[0013] The chemical catalytic effect improves gas sensing performance by increasing the ionization of oxygen and the adsorption of oxygen ions on the surface of the semiconductor sensing material through the spillover action of the precious metal catalyst.
[0014] The electronic effect is that an energy barrier is formed at the interface due to the junction of the semiconductor and the metal, which increases the initial resistance of the semiconductor sensing material and consequently improves gas sensing performance (sensitivity Rs is measured as Ra / Rg, where Ra is the electrical resistance when exposed to air, i.e., the initial resistance, and Rg is the lowest resistance value after the measurement gas is injected).
[0015] However, due to the second effect, the electronic effect, the initial resistance Ra of the semiconductor material increases significantly.
[0016] Recently, as the demand for high-sensitivity gas sensors has increased, metal nanoparticles are being combined with N-type semiconductors in various forms to improve the sensitivity of gas sensors.
[0017] Among these composite nanoparticles, metal / semiconductor core / shell structured nanoparticles have recently attracted significant attention due to their high gas reactivity. However, they still lack selectivity for specific gases.
[0018] In response to these demands, composites of metal nanoparticles and N-type semiconductors are being attempted to improve the sensitivity of gas sensors to hydrogen gas by forming a core of a Pd-Au binary alloy with hydrogen absorption capabilities. However, among these composite nanoparticles, metal / semiconductor core / shell structured nanoparticles still have low selectivity for specific gases despite their high gas reactivity.
[0019] The method for manufacturing a thin-film high-activity gas sensor according to Patent Document 1 is characterized by comprising a process of applying a composite nanoparticle, which consists of a metal nanoparticle core and a metal oxide nanoparticle shell layer covering the surface of the core, onto an electrode circuit board, and the thin-film high-activity gas sensor manufactured by the method for manufacturing a thin-film high-activity gas sensor is recognized to have excellent effects such as high gas reactivity.
[0020] However, conventional semiconductor gas sensors operate simultaneously with other gases such as CO, NO, CH4, and VOCs, resulting in a lack of selective detection.
[0021] Although the composite nanoparticle hydrogen gas sensing material with a Pd alloy / oxide semiconductor core-shell structure and the semiconductor gas sensor for hydrogen gas sensing using the same according to Patent Document 2 exhibited characteristics of selectively reacting to hydrogen gas, it was difficult to expect further improvement in sensitivity due to the problem of partial oxidation of the surface of the Pd alloy core.
[0022] With the recent increase in hydrogen usage, such as in hydrogen electric vehicles, the demand for gas sensors to detect hydrogen gas leaks has increased accordingly.
[0023] However, in the case of semiconductor gas sensors, their use is inevitably limited because they react to most reducing gases (H2, CO, CH4, VOCs, etc.).
[0024] In addition, electrochemical and optical gas sensors are currently used for hydrogen gas detection in addition to semiconductor gas sensors; however, electrochemical sensors have a short lifespan, while optical sensors have the problems of large size and high cost.
[0025] Therefore, there is a need to develop a relatively inexpensive semiconductor gas sensor with excellent reactivity and selectivity toward hydrogen gas. Prior art literature
[0026] Korean Registered Patent No. 10-1074917 Korean Registered Patent No. 10-2287604 The problem to be solved
[0027] The present invention has been devised to solve the problems of the prior art as described above. The purpose of the present invention is to provide a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure that has excellent selectivity for hydrogen gas, excellent durability, and a low operating temperature, and a method for manufacturing the same.
[0028] In addition, the present invention aims to provide a semiconductor gas sensor for detecting hydrogen gas using a hydrogen gas sensing material having excellent selectivity for the hydrogen gas. means of solving the problem
[0029] To achieve the above objective, the hydrogen gas sensing material according to the present invention, having an Ag-Pd-Au alloy core and a metal oxide shell structure, is characterized by comprising: a core made of Ag-Pd-Au alloy nanoparticles; and a shell layer made of a metal oxide and surrounding the core.
[0030] Here, the core is characterized by the Ag-Pd-Au alloy nanoparticles being composed of any one of the weight ratios of 1:1:1, 1:1:3, and 1:1:5.
[0031] Here, the shell layer is characterized by being composed of an N-type semiconductor or a P-type semiconductor metal oxide.
[0032] Here, the shell layer is characterized by being composed of one or more selected from SnO2, TiO2, ZnO, WO3, In2O3, V2O5, and RuO.
[0033] Here, the shell layer is characterized by being composed of ZnO.
[0034] In addition, the method for manufacturing a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure according to the present invention is characterized by comprising: (1) a core forming step of synthesizing Ag-Pd-Au alloy nanoparticles to form a core; and (2) a shell layer forming step of forming a shell layer of a metal oxide on the Ag-Pd-Au alloy nanoparticles.
[0035] In addition, the semiconductor gas sensor for detecting hydrogen gas according to the present invention is characterized by comprising: an electrode circuit board; and a thick film formed by applying a plurality of hydrogen gas sensing materials having an Ag-Pd-Au alloy core and a metal oxide shell structure to the electrode circuit board. Effects of the invention
[0036] According to the above configuration, the hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure according to the present invention, the method for manufacturing the same, and the semiconductor gas sensor for hydrogen gas sensing using the same have the advantage of significantly improving selective reactivity and reaction sensitivity to hydrogen gas by applying Ag-Pd-Au ternary alloy nanoparticles having absorption characteristics for hydrogen gas as a core, thereby allowing hydrogen gas to be easily adsorbed onto the surface of the metal oxide shell layer, and at the same time promoting the oxidation reaction between the oxygen ions adsorbed on the shell layer and the hydrogen gas, thereby greatly changing the electrical resistance. Brief explanation of the drawing
[0037] FIG. 1 is a structural diagram of a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure according to an embodiment of the present invention. FIG. 2 is a flowchart of a method for manufacturing a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure according to an embodiment of the present invention. FIG. 3 is a TEM photograph of a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure manufactured by the manufacturing method according to an embodiment of the present invention. FIG. 4 is a graph of the X-ray diffraction analysis results of a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure manufactured by the manufacturing method according to an embodiment of the present invention. FIG. 5 is a structural diagram of a semiconductor gas sensor for hydrogen gas detection using a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure according to an embodiment of the present invention. FIG. 6 is a graph of the electrical resistance change curve of a semiconductor gas sensor according to Examples 1 to 3 and a comparative example of the present invention. FIG. 7 is an embodiment of the present invention. Graphs showing the change curve of the temperature-dependent sensitivity (Rs) of the semiconductor gas sensor according to 1 to 3 and the comparative example, and Figure 8 is a graph of the temperature-dependent sensitivity (Rs) of the semiconductor gas sensor for various reaction gases according to Example 2 of the present invention. Specific details for implementing the invention
[0038] Hereinafter, with reference to the embodiments illustrated in the drawings, a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure according to the present invention, a method for manufacturing the same, and a semiconductor gas sensor for detecting hydrogen gas using the same will be described in detail.
[0040] [Hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure]
[0041] FIG. 1 is a structural diagram of a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure according to an embodiment of the present invention.
[0042] Referring to FIG. 1, a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure according to one embodiment of the present invention includes a core (10) and a shell layer (20).
[0043] The above core (10) is composed of a combination of elements having absorption characteristics for hydrogen gas, and in the present invention, it is composed of Ag-Pd-Au ternary alloy nanoparticles.
[0044] Generally, Pd nanoparticles exhibit hydrogen gas absorption characteristics, but when exposed to the atmosphere at temperatures above several hundred degrees, they oxidize to form PdO and lose their hydrogen gas absorption properties; therefore, Pd nanoparticles alone are not desirable for semiconductor gas sensors operating at temperatures above several hundred degrees.
[0045] However, Ag-Pd-Au alloy nanoparticles as in the present invention have high resistance to oxidation at high temperatures, and thus have the advantage of exhibiting excellent hydrogen gas absorption characteristics even in semiconductor gas sensors operating at temperatures above several hundred degrees.
[0046] In addition, in the present invention, the core (10) made of the Ag-Pd-Au alloy nanoparticles is disposed inside a shell layer (20) made of a metal oxide, so there is an advantage that the Ag-Pd-Au alloy nanoparticles do not deform even when used for a long time at a high temperature.
[0047] Meanwhile, in an embodiment of the present invention, the core (10) may be composed of Ag-Pd-Au alloy nanoparticles in a weight ratio of any one of 1:1:1, 1:1:3, and 1:1:5.
[0048] That is, the core (10) according to embodiments 1 to 3 of the present invention is composed of Ag1Pd1Au1, Ag1Pd1Au3, and Ag1Pd1Au5, respectively.
[0049] The effects according to each embodiment of the core (10) having the above weight ratio will be described later.
[0050] The shell layer (20) above is configured to surround the core (10) and is made of a metal oxide in the present invention.
[0051] The shell layer (20) may be an N-type semiconductor or a P-type semiconductor metal oxide, and it is preferable that the shell layer (20) be composed of N-type semiconductor metal oxide nanoparticles with excellent reactivity to gas.
[0052] In N-type semiconductor metal oxide nanoparticles, the main charge carrier is the electron.
[0053] These electrons ionize surrounding oxygen, adsorb oxygen ions onto the surface of N-type semiconductor metal oxide nanoparticles, and form an electron depletion layer on the surface of the metal oxide nanoparticles.
[0054] As a result, the electrical resistance of metal oxide nanoparticles increases significantly.
[0055] At this time, when reducing gases including hydrogen gas (CO, CH4, VOCs, etc.) are introduced, they combine with oxygen ions and oxidize these gases, while electrons captured by oxygen ions are returned to the interior of the metal oxide nanoparticles, so the electrical resistance of the metal oxide nanoparticles decreases significantly.
[0056] By detecting these changes in electrical resistance, the presence and concentration of reducing gas can be measured.
[0057] However, in principle, it is difficult to expect selective reactions depending on the type of reducing gas using only metal oxide nanoparticles.
[0058] If an Ag-Pd-Au alloy exhibiting hydrogen absorption characteristics is placed within metal oxide nanoparticles, the Ag-Pd-Au alloy selectively attracts a large amount of hydrogen gas, and more oxidation reactions of hydrogen gas can occur on the surface of the metal oxide nanoparticles.
[0059] As a result, composite nanoparticles having an Ag-Pd-Au alloy core and a metal oxide shell structure exhibit much higher reactivity to hydrogen gas compared to other gases.
[0060] In addition, the composite nanoparticle having an Ag-Pd-Au alloy core and a metal oxide shell structure has the characteristic that there is no concern that the Ag-Pd-Au alloy nanoparticle will deform even when used for a long time at high temperatures, because the Ag-Pd-Au alloy nanoparticle that attracts hydrogen gas is placed inside a shell layer (20) made of metal oxide in the form of a core (10).
[0061] In particular, the surface of the core (10) made of Ag-Pd-Au alloy nanoparticles can be partially oxidized to prevent a decrease in hydrogen gas sensitivity.
[0062] In an embodiment of the present invention, the shell layer (20) may be composed of one or more selected from SnO2, TiO2, ZnO, WO3, In2O3, V2O5, and RuO.
[0063] In particular, the shell layer (20) is preferably made of ZnO due to the ease of forming a uniform shell layer.
[0064] The shell layer (20) may have a thickness of 10 to 100 nm to stabilize the core (10) and allow hydrogen gas to pass through.
[0066] [Method for manufacturing a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure]
[0067] FIG. 2 is a flowchart of a method for manufacturing a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure according to an embodiment of the present invention.
[0068] Referring to FIG. 2, a method for manufacturing a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure according to one embodiment of the present invention includes a core forming step (S10) and a shell layer forming step (S20).
[0069] The above core formation step (S10) is a step for synthesizing Ag-Pd-Au alloy nanoparticles.
[0070] An example of the core formation step (S10) according to the present invention is as follows.
[0071] First, prepare a mixed solution of 40 mL of 15 mM CTAB (cetyltrimethylammonium bromide) aqueous solution and 5 mL of 15 mM CTAC (cetyltrimethylammonium chloride) aqueous solution, add 1 mL of 10 mM HAuCl4 aqueous solution, 1 mL of 10 mM H2PdCl4 aqueous solution, and 10 mM AgNO3 aqueous solution to this, and stir for 5 minutes.
[0072] 0.57 mL of a 100 mM sodium citrate aqueous solution was added to this solution as a reducing agent, and the reduction reaction was carried out in an electric oven at 90°C for 24 hours to prepare an Ag1Pd1Au1 alloy nanoparticle colloid.
[0073] To prepare Ag1Pd1Au3 and Ag1Pd1Au5 alloy nanoparticle colloids, 10 mM HAuCl4 aqueous solution was changed to 3 mL and 5 mL, respectively, and other conditions were performed in the same manner as the method for preparing Ag1Pd1Au1 alloy nanoparticle colloids.
[0074] Figure 3 (a) is a TEM image of Ag-Pd-Au alloy nanoparticles synthesized by a manufacturing method according to an embodiment of the present invention, and the particle size is 15 to 20 nm.
[0075] The shell layer formation step (S20) is a step of forming a shell layer (20) of a metal oxide on the Ag-Pd-Au alloy nanoparticles.
[0076] An example of the shell layer forming step (S20) according to the present invention is as follows.
[0077] 60 mL of distilled water is placed in a 100 mL glass container, and 0.15 g of CTAB is added and dissolved by vigorously stirring at 60°C. Then, 5 mL each of the three types of Ag-Pd-Au alloy nanoparticle colloid solutions synthesized above, namely Ag1Pd1Au1, Ag1Pd1Au3, and Ag1Pd1Au5, is mixed.
[0078] Next, 1 mL of 200 mM ascorbic acid aqueous solution and 2 mL of 200 mM Zn(NO3)2 aqueous solution are added and stirred for 10 minutes, then 2 mL of 200 mM HMTA (hexamethylenetetramine) aqueous solution is added.
[0079] Three types of Ag-Pd-Au / ZnO core / shell nanoparticles were synthesized, respectively: Ag1Pd1Au1 / ZnO (Example 1), Ag1Pd1Au3 / ZnO (Example 2), and Ag1Pd1Au5 / ZnO (Example 3), by sealing a glass container containing the above mixed solution and reacting it in an electric oven at 86°C for 8 hours.
[0080] The synthesized nanoparticle colloidal solution is collected by centrifuging at a rotational speed of 15,000 rpm for 20 minutes, washed three times with distilled water, and dried at 60°C.
[0081] FIG. 3 (b) is a TEM image of Ag-Pd-Au (alloy) / ZnO (metal oxide) core-shell structure composite nanoparticles synthesized by a manufacturing method according to an embodiment of the present invention, with an overall particle size of 60 to 70 nm and a ZnO shell layer thickness of 35 to 40 nm.
[0082] Figure 4 is a graph of the X-ray diffraction analysis results of synthesized Ag-Pd-Au (alloy) / ZnO (metal oxide) core-shell structure composite nanoparticles prepared by the manufacturing method according to one embodiment of the present invention, and for comparison, the X-ray diffraction analysis results of pure ZnO nanoparticles and Ag1Pd1Au1 alloy nanoparticles are also shown.
[0083] From these results, it can be confirmed that the Ag-Pd-Au alloy core and ZnO shell are formed with high crystallinity in all examples, and that the X-ray diffraction intensity of the Ag-Pd-Au alloy increases as the Au composition of the Ag-Pd-Au alloy core increases.
[0085] [Semiconductor gas sensor for hydrogen gas detection using a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure]
[0086] FIG. 5 is a structural diagram of a semiconductor gas sensor for detecting hydrogen gas using a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure according to an embodiment of the present invention.
[0087] Referring to FIG. 5, a semiconductor gas sensor for detecting hydrogen gas according to one embodiment of the present invention includes an electrode circuit board (100) and a thick film (200).
[0088] The above electrode circuit board (100) can be manufactured as an alumina (Al2O3) substrate with a platinum electrode circuit printed thereon, which serves as the base of a semiconductor gas sensor.
[0089] The above-mentioned thick film (200) is formed by applying a plurality of hydrogen gas sensing materials (1) having the above-mentioned Ag-Pd-Au alloy core and metal oxide shell structure to the above-mentioned electrode circuit board (100).
[0090] A semiconductor gas sensor according to one embodiment of the present invention can be manufactured in the following manner.
[0091] 10 mg of powder of Ag-Pd-Au (alloy) / ZnO (metal oxide) composite nanoparticles (Examples 1 to 3) and pure ZnO nanoparticles (Comparative Example 1) and 10 µl of alpha-terpinol solution are placed in a mortar and pestle and mixed to form a paste.
[0092] This composite nanoparticle paste is applied by squeeze printing on an alumina electrode circuit board (100) on which a platinum electrode circuit is printed, dried at 60°C until a constant weight is achieved, and then fired at 500°C for 2 hours to form a composite nanoparticle thick film (200).
[0094] [Sensitivity Measurement of Semiconductor Gas Sensors]
[0095] The sensitivity to various gases was measured using a semiconductor gas sensor manufactured by the method described above.
[0096] During the test, the O2 concentration was adjusted to 11.5%, and the detection characteristics were evaluated by measuring the change in resistance caused by the injection of the measurement gas.
[0097] The sensitivity (reactivity) Rs of the sensor to the gas being measured was calculated as Ra / Rg, where Ra is the initial resistance value in air before the injection of the gas being measured, and Rg is the resistance value at the lowest value after the injection of the gas being measured.
[0098] The gases to be measured were hydrogen (H2), ethanol (C2H5OH), acetone (CH3COCH3), acetaldehyde (CH3CHO), methane (CH4), and carbon monoxide (CO), and the measurement temperature was set to 200–400℃.
[0099] The concentration of the measured gas was tested at various concentrations ranging from 5 ppm to 100 ppm, and the sensitivity was compared with other gases using the sensitivity value at a concentration of 100 ppm for each measured gas.
[0101] [Comparative Example 1]
[0102] To prepare pure ZnO nanoparticles, a mixed solution was prepared by adding 60 mL of distilled water, 1.465 g of CTAB, 0.35 g of ascorbic acid, 0.564 g of HMTA (hexamethylenetetramine), and 21.2 g of Zn(NO3) to a 100 mL glass container, and ZnO nanoparticles were synthesized by reacting the solution at 86°C for 8 hours. The synthesized nanoparticle colloidal solution was centrifuged to recover only the ZnO nanoparticles, washed three times with distilled water, and dried at 60°C to obtain ZnO nanoparticles.
[0104] [Examples 1 to 3]
[0105] As described above, three types of Ag-Pd-Au / ZnO core / shell nanoparticles, Ag1Pd1Au1 / ZnO (Example 1), Ag1Pd1Au3 / ZnO (Example 2), and Ag1Pd1Au5 / ZnO (Example 3), are synthesized using a method for manufacturing a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure, which includes a core formation step (S10) and a shell layer formation step (S20).
[0107] [Evaluation of Gas Detection Characteristics of Examples and Comparative Examples]
[0108] FIG. 6 is a graph of the change in electrical resistance of a semiconductor gas sensor according to embodiments 1 to 3 and a comparative example of the present invention.
[0109] That is, Figure 6 shows the sensitivity to hydrogen gas for the Ag-Pd-Au (alloy) / ZnO (metal oxide) core-shell structure nanoparticle gas sensors of Examples 1 to 3 and the pure ZnO gas sensor of Comparative Example 1, measured in a temperature range of 200 to 400°C, and represents the change in electrical resistance values according to the change in hydrogen gas concentration from 100 ppm to 5 ppm.
[0110] At a measurement temperature of 400°C or lower, the Ag-Pd-Au / ZnO core-shell structured nanoparticle gas sensors of Examples 1 to 3 all exhibited better H2 gas reactivity than the pure ZnO nanoparticle sensor of Comparative Example 1.
[0112] [Comparison of Sensitivity According to Measurement Temperature of Examples and Comparative Examples]
[0113] FIG. 7 is a graph of the change curve of the sensitivity (Rs) of a semiconductor gas sensor according to Examples 1 to 3 and a comparative example of the present invention.
[0114] That is, Figure 7 shows the sensitivity of the sensors of Examples 1 to 3 and Comparative Example 1 to 100 ppm hydrogen gas at different measurement temperatures.
[0115] The Ag1Pd1Au1 / ZnO core-shell structure nanoparticle sensor (Example 1) exhibited a maximum sensitivity (Rs) of 68 at a measurement temperature of 300°C.
[0116] The maximum reactivity of the Ag1Pd1Au3 / ZnO and Ag1Pd1Au5 / ZnO core-shell composite nanoparticle sensors (Examples 2 and 3), in which the composition of the Ag-Pd-Au core was 1:1:3 and 1:1:5, respectively, was observed at 300°C, and the sensitivity (Rs) to hydrogen gas was 418 and 245, respectively, indicating that Ag1Pd1Au3 / ZnO of Example 3 has the best hydrogen gas reactivity.
[0117] This sensitivity value is 70 times higher than that of the comparative example ZnO nanoparticle gas sensor.
[0119] [Comparison of Sensitivity with Hydrogen Gas and Other Gases in Example 2]
[0120] Figure 8 is a graph of the sensitivity (Rs) of a semiconductor gas sensor according to Example 2 of the present invention to various reaction gases at different temperatures.
[0121] That is, Figure 8 is a bar graph illustrating the temperature-dependent sensitivity of the Ag1Pd1Au3 / ZnO core-shell structure nanoparticle semiconductor gas sensor of Example 2 with respect to 100 ppm of hydrogen, ethanol, acetone, acetaldehyde, methane, and carbon monoxide gases.
[0122] At 300°C, the optimal operating temperature of the Ag1Pd1Au3 / ZnO core-shell structure nanoparticle semiconductor gas sensor, the reactivity to hydrogen (Rs=418) is 4 times higher than that of ethanol gas, 24 times higher than that of acetone gas, 26 times higher than that of acetaldehyde gas, 140 times higher than that of methane gas, and 26 times higher than that of CO gas, confirming that it has excellent selectivity for hydrogen gas.
[0124] The hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure described above and illustrated in the drawings, the method for manufacturing the same, and the semiconductor gas sensor for hydrogen gas detection using the same are merely one embodiment for carrying out the present invention and should not be interpreted as limiting the technical scope of the present invention. The scope of protection of the present invention is determined only by the matters described in the following claims, and embodiments that are improved and modified without departing from the gist of the present invention shall be deemed to fall within the scope of protection of the present invention insofar as they are obvious to those skilled in the art to which the present invention belongs. Explanation of the symbols
[0125] 1. Hydrogen gas sensing material 10 cores 20 shell layers S10 Core formation stage S20 Shell layer formation step 100 electrode circuit boards 200 thick film
Claims
Claim 1 A hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure, comprising: a core made of Ag-Pd-Au alloy nanoparticles; a shell layer made of a metal oxide and surrounding the core; wherein the shell layer is made of ZnO, and the core is characterized in that the Ag-Pd-Au alloy nanoparticles are composed in a weight ratio of 1:1:
3. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 A method for manufacturing a hydrogen gas sensing material having an Ag-Pd-Au alloy core and a metal oxide shell structure according to claim 1, comprising: (1) a core forming step of synthesizing Ag-Pd-Au alloy nanoparticles to form a core; and (2) a shell layer forming step of forming a shell layer of a metal oxide on the Ag-Pd-Au alloy nanoparticles. Claim 7 A semiconductor gas sensor for detecting hydrogen gas, characterized by comprising: an electrode circuit board; and a thick film formed by applying a plurality of hydrogen gas sensing materials having an Ag-Pd-Au alloy core and a metal oxide shell structure according to claim 1 to the electrode circuit board.
Citation Information
Patent Citations
Alloy Bonding Wire Based on Ag-Au-Pd
KR101583865B1
P-type semiconductor-coated composite nanoparticles sensing materials for semiconductor gas sensor
KR1020160045188A
Pd-alloys / metallic oxide semiconductors core-shell structure nanoparticles for detecting hydrogen gas and semiconductor type gas sensor using the same
KR1020210054202A